PERTARUNGAN SIMBOLIK DALAM WACANA BANTUAN KHUSUS MAHASISWA - Mohamad Jazeri (LITERA, 2009)
This study aims to describe forms of, strategies in, and factors causing symbolic conflicts in the discourse of Special Aids for Students (SAS). The data sources were texts on SAS in mass media. This study employed the Critical Discourse Analysis (CDA) by Fairclough. The data were analyzed in three steps, i.e. text analysis (description), process analysis (interpretation) and socio-cultural practice analysis (explanation). The findings can be explained as follows. First, the forms of symbolic conflicts are the introduction and refusal of meaning, logic, perspective, and value. Second, the strategies of symbolic conflicts include making them subtle or vague and making them positive or natural. Third, the factors causing symbolic conflicts include differences in habits and social structure and those in discourse executors’ interests.